A replica algorithm based on popularity for P2P streaming media - Yang Ge; Gao Bing; Huang Jing; He Hui (Dianzi Jishu Yingyong, 2018)
In this paper，a new formula of popularity was proposed. It included the term deficit bandwidth and was based on the new popularity. Those streaming media files which need to be replicated were determined. A concept named comprehensive performance indicators was proposed. Peers were sorted by their comprehensive performance indicators and those peers with high comprehensive performance indicators had priority to place these popular files. Replacement algorithm would be carried out if there was no enough space to cache the new file, and the file which had largest ratio of its duplicates to the desired duplicates would be replaced by the new file. Experimental results show that the workload of the proposed algorithm, compared with proportional replication algorithm, is in steady conditions earlier about 13% in advance and is smaller. Its workload in steady-state condition is about 33.3% of the workload of the proportional replication algorithm. Meanwhile, more of one in a thousand peers has the desired requested rates in steady-state. Besides, the proposed algorithm has more stationary transient process.